Examination of nitrogenous compounds in Hungarian bio-musts - Kállay, M.; Nyitrainé Sárdy, D. (International Journal of Horticultural Science, 2005)
There has not been any research done on the musts from organic grapes. As a result of the special technologies in organic farming we can expect bio-musts to have a different quantitative and qualitative composition of nitrogen compounds from that of traditional musts. In our present essay we deal with the tests of nitrogenous compounds (assimilable nitrogen content, aminoacid, biogenic amine content) in musts from Hungary’s bio-wine cellars. Our results show that the change in procedures has resulted in neither quantitative nor qualitative changes in the nitrogenous compounds of bio-musts.